Interaction and problems in the abaca industry in Region VIII, Philippines - Milagros C. Bales; Karen Luz P. Yap; Fatima T. Baliña; Leomarich F. Casinillo (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration)
This article aims to elucidate the level of interaction among the different players in the abaca business enterprise in Region VIII, Philippines. The study used a survey method that gathered primary data from farmers, Local Government Units (LGUs), traders, innovators from universities, processors, and non-government organizations. Appropriate sampling methods were employed in determining the sample sizes of different players, and the research instrument used to determine the interaction process is a developed questionnaire that involved a Likert scale. The data were analyzed using statistical measures such as count and average mean and presented in tabular form and network analysis. The results showed that abaca farmers have minimal to no interaction with the other key players except with the local traders. With that, the main problem for abaca farmers is the lack of innovative information to improve their production. Local traders interact with farmers moderately but have weak interaction with the Philippine Fiber Industry Development Authority (PhilFIDA) in terms of provision for research, education, and support services, among others. LGUs moderately interact with farmers but have no interaction at all with other Abaca key players. Moreover, PhilFIDA staff only have a moderate interaction with abaca farmers, and local traders rarely interact with PhilFIDA staff. Likewise, PhilFIDA’s interaction with State Universities and Colleges (SUCs) is weak and SUCs have moderate interaction with farmers and the LGUs. Conclusively, the interactions among the players of the abaca industry are generally weak which can be strengthened through institutionalizing a system where stakeholders can work together for the common good and obtain a sustainable supply chain.